EPIDEMIOLOGY OF DOWN’S SYNDROME & Β- THALASSEMIA IN INDIA - Gajbhiye, Nilima; Gaitonde, Ritika (International Journal of Research -GRANTHAALAYAH, 2022)
Down’s syndrome and Beta (β) Thalassemia are commonly prevalent genetic diseases worldwide. Down’s syndrome is predominantly caused by an extra copy of chromosome 21 or trisomy 21. Maternal age above 35 years significantly increases the chances of a Down’s syndrome birth. In India, there are approximately 21,000 Down’s syndrome births every year. β-Thalassemia is a blood disorder caused by abnormal synthesis of the β chains of hemoglobin. India has over 35-45 million carriers of this disease. This is a survey-based study, which aims to understand the epidemiology of Down’s syndrome and Beta Thalassemia in the Indian population. This online survey was answered by 297 Indian or Indian origin adults. Both females and males were the respondents. Results of the study indicated that prevalence of Down’s syndrome is low in India while that of β-thalassemia is moderate. The correlation between the maternal and paternal ages at the time of birth of a Downs syndrome affected person was determined and the analyses showed that there was a positive correlation.